Motivation and Workload of Nurses with Nurse Performance in Handling Events of Corona Virus (Covid-19) - M Arifki Zainaro; Ridwan Ridwan; Usastiawaty Cik Ayu Saadiah Isnainy (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Coronavirus Disease 2019 (COVID-19) is a new type of disease that has never been previously identified in humans. The virus that causes COVID-19 is called Sars-CoV-2. As part of the front line in dealing with COVID-19 cases, many health care workers experience fatigue both physically and mentally. Their high workload in handling COVID-19 cases, the scarcity of Personal Protective Equipment (PPE) facilities and insufficient nutritional needs, decrease their immunity, so the risk of contracting the virus increases. To determine the relationship between motivation and workload of nurses and the performance of nurses in handling the coronavirus (COVID-19) incident at Pertamina Bintang Amin Hospital, Bandar Lampung. This type of research is a quantitative, research design analytic survey with a cross-sectional approach. The population and sample of this study were all nurses who served in the inpatient room of Pertamina Bintang Amin Hospital, Bandar Lampung, with as many as 58 respondents. Results Of the 58 respondents, the motivation and workload that were said to be poor with the performance of nurses were 21 respondents (36.2%), while the motivation and workloads that were said to be good with the performance of nurses were 37 respondents (63.8%). The results of statistical tests showed that the p-value = 0.003 was smaller than the alpha value (p less than 0.05). There is a significant relationship together between motivation and workload with the performance of nurses in handling the coronavirus (COVID-19) incident at Pertamina Bintang Amin Hospital, Bandar Lampung. It is hoped that the hospital management will continue to maintain the level of motivation for health workers, especially nurses, to get additional incentives for nurses and workloads to take time off for nurses who work during working hours and the performance of nurses in carrying out actions in accordance with the SOP for patients suffering from Covid 19.